Probing the Effects of Local Frustration in the Folding of a Multidomain Protein. Issue 15 (23rd July 2021) - Pagano, Livia; Malagrinò, Francesca; Visconti, Lorenzo; Troilo, Francesca; Pennacchietti, Valeria; Nardella, Caterina; Toto, Angelo; Gianni, Stefano
Graphical abstract: Highlights: Whirlin PDZ1-PDZ2 tandem as a case study of multidomain folding. Extensive mutational analysis of PDZ1 in isolation and in supramodular structure. Early events of folding are malleable and sculpted by protein frustration. Analysis of protein frustration patterns supports funneled energy landscape theory. Abstract: Our current knowledge of protein folding is primarily based on experimental data obtained from isolated domains. In fact, because of their complexity, multidomain proteins have been elusive to the experimental characterization. Thus, the folding of a domain in isolation is generally assumed to resemble what should be observed for more complex structural architectures. Here we compared the folding mechanism of a protein domain in isolation and in the context of its supramodular multidomain structure. By carrying out an extensive mutational analysis we illustrate that while the early events of folding are malleable and influenced by the absence/presence of the neighboring structures, the late events appear to be more robust. These effects may be explained by analyzing the local frustration patterns of the domain, providing critical support for the funneled energy landscape theory of protein folding, and highlighting the role of protein frustration in sculpting the early events of the reaction.